A flexible yet wear-resistant co-citrate elastomer for on-demand disposable patch sensors. Issue 29 (6th July 2020) - Kim, Do-Gwan; Ahn, Dowon; Kim, Kang-Han; Jeong, Yong-Cheol
Abstract : Herein, we report a wearable strain sensor, composed of a water-soluble metal electrode and a pH-sensitive encapsulation layer, with conforming flexibility and super wear-resistance. Abstract : Herein, we report a wearable strain sensor, composed of a water-soluble metal electrode and a pH-sensitive encapsulation layer, with conforming flexibility and super wear-resistance. This is enabled by a polysilsesquioxane-incorporated co-citrate elastomer that dissolves in a well-controlled manner that is pH sensitive. Additionally, the organic–inorganic hybrid network structures provide an enhanced surface hardness of 8H@250 g without sacrificing flexibility. Different from currently available transient electronic devices, the unique features of the encapsulation material give rise to exceptional operational reliability in daily life, as well as selective disposability upon exposure to specific stimuli. In this study, the pH-sensitive dissolution behavior and thermomechanical properties of the co-citrate elastomer are characterized via varying the polysilsesquioxane crosslinker content. Finally, we demonstrate an on-demand disposable strain sensor that monitors fine movements of the human body and can be disposed of entirely via laundering. This concept of on-demand disposable electronics will be useful for cutting-edge electronic circuit board technology and advanced healthcare devices.